The World Bank Annual report 1985 - World Bank Inspection Panel (Washington, D.C. : World Bank)
The book contains the annual report of the World Bank for the year 1985.
Description based on: Aug. 1, 1996 to July 31, 1997 issue.
usc 11/04/2019
Ref
Keywords: Banks and banking, International; Economic assistance; World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency; International finance